Międzykulturowe badania nad przywództwem - program badawczy GLOBE - Mączyński, Jerzy (Cross-cultural study on leadership - globe research project, 2006)
In the past decade there was growing interest in cross-cultural research on leadership. There was also an increasing awareness of the need for a better understanding of the way in which leadership is performed in various cultures and the need for an empirically grounded theory to explain divergent leader behaviour and effectiveness across cultures. The comparison of some of the research results from the GLOBE project with existing studies revealed some interesting aspects of leadership in Poland as compared to Western cultures. The findings presented in this paper may contribute to a better understanding of culturally driven differences in leadership and serve as a source of information about organizational and management practices in Poland as compared to Western societies. These data might be valuable not only to scholars who study cross-cultural issue in organizations, management, and leadership but also to practitioners both in Western organizations operating in Poland and Polish firms operating in Western cultures.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 77-88